Research progress of combined auricular acupoint therapy for the treatment of headache in hypertensive patients (耳穴联合疗法治疗高血压患者头痛研究进展) - ZHANG Yuanyuan (张园园); LI Yuye (李玉叶); ZHOU Xiaoyan (周晓艳); DOU Jinjie (窦金杰); CUI Liu (崔柳); ZHANG Yue (张悦); SUN Tingting (孙婷婷) (Association of Integrative Nursing, 2021)
Hypertension is a common chronic disease, and headache, as one of the clinical symptoms of hypertension, has recurrent attacks and seriously affects the quality of life of patients. In recent years, studies have applied the combination of auricular pressure massage, ear tip bloodletting and auricular point pressing to treat hypertensive headache with good efficacy, improving patients' comfort and quality of life, which is widely used in clinical practice. This article reviewed studies on the efficacy of combined auricular acupoint therapy in the treatment of hypertensive headache patients. (高血压是一种常见慢性疾病, 头痛作为高血压的常见临床症状之一, 反复发作会严重影响患者生存质量。近年来, 耳穴按摩、耳尖放血、耳穴贴压联合治疗高血压引起的头痛取得了良好效果, 提高了患者的舒适度和生活质量, 在临床上应用广泛。本文综述了耳穴联合疗法治疗高血压患者头痛相关研究, 旨在为临床干预高血压引起的头痛提供参考。)